Innovative approach of nanoformula moisturizer applications in atopic dermatitis: a review - Nyoman Suryawati; Made Wardhana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
The skin barrier defect is the first step in the development of atopic dermatitis (AD). Various therapeutic guidelines recommend using moisturizers to maintain the skin barrier and the prevention of AD. The use of a moisturizer in the form of barrier cream is considered to improve the skin barrier. However, this dosage form is occlusion and has an oily texture, resulting in patient noncompliance with therapy. Various techniques were developed to improve patient compliance in applying topical preparations, one of which is by developing nanotechnology. Recent studies aim to develop nanoformula preparations because they can help deliver drug molecules to specific targets with minimize side effects. The application of nanoformula moisturizer is promising in the management of AD because of its ability to reduce water loss and prevent irritation and produce formulations with a thinner texture to increase therapeutic compliance in AD patients.